Course features epidemic process HIV infection in Kharkiv region - Nikolaeva, L; Majstat, T; Podavalenko, A; Kusch, D (Annals of Mechnikov’s Institute, 2020)
Introduction. In the context of the transformation of the spheres of human living epidemic HIV-infection continues. According to the intensity of the epidemic process of HIV-infection, Ukraine takes one of the first places among the European countries. The epidemic process of the infection is concentrated mainly on the high-risk groups, and there is uneven prevalence. Besides in most cases this distribution can not be explained by the social and economic characteristics of certain territories. Kharkiv region belongs to the territory of Ukraine with the lowest prevalence level of HIV-infection. Though in terms of the social and economic crisis due to hostilities in the east of the country, which the region borders, the epidemic situation may significantly become worse. Work objective: to study the peculiarities of the course of the epidemic process of HIV-infection for the period from 1987 till 2015 in Kharkiv region that will improve the epidemiological surveillance of the infection and develop appropriate preventive measures in modern conditions. Material & methods. The studies were conducted in Kharkiv region, which is a big industrial and administrative center. The city of Kharkiv is located at the crossroads of drug trafficking from Asia and Russia. The reportings and analytics of the Kharkiv regional center for prevention and control of AIDS and the Ministry of Health of Ukraine for the period of 1987 – 2015 were used in the research. The analysis of incidence of HIV prevalence, structure of transmission routes and sex-age groups were carried out using descriptive and evaluative and analytical ways of epidemiological research method. Results & discussion. During 1987 – 2015 in Kharkiv region there were officially registered 7868 cases of HIV-infection what was equal to 4.0 % of the registered cases in Ukraine. Since 1996 a marked upward tendency of the incidence of HIV infection in Kharkiv region (growth rate – +7.0 %), and on the whole in Ukraine (growth rate – +14.0 %). Herewith of incidence of HIV-infection in the region were lower than on the whole in Ukraine (accordingly 2.4 – 23.7 and 10.6 – 47.1 per 100 000 population). Almost all of the administrative territories of Kharkiv region have been involved into the epidemic process of HIV-infection, but in districts of the region the incidence of HIV-infection, AIDS and mortality were in 1.4 – 2.7 times higher than in Kharkiv itself. The measures directed at the prevention of HIV-infection in the groups of risk were actively being taken during the supervision in the region. Due to the collaboration of the executive authorities and local government, departmental structures, medical community and public organizations directed at the suspension of HIV-infection/AIDS epidemic in the region we managed to stabilize a little an epidemical situation on HIV-infection. For the period of 1987 – 2015 in the region there was defined the increase in the number of the infected women (from 12.9 % to 41.0 %) and the decrease of the number of men (from 87.1 % to 59.0 %) what led to the change of the ratio of the number of women with the number of men in accordance with 1:7 (1996) and 1:1.5 (2015). There were adultpatients withHIV-infection (79.5 – 84.9 %) in4-5times more thanchildren underthe age of 14(15.1 –20.5 %). The largest proportion ofHIV-infected peoplein the age group of 25–49 years(60.0 – 72.2 %) and the lowest–15–17 years(0.1 – 1.0 %). In different periods of the current epidemic process of HIV-infection the ratio of parenteral, sexual and vertical routes of transmission considerably changed. At the beginning of the epidemic the incidence level of HIV-infection has been significantly affected by the drugs spreading and an increase in vulnerable groups of injecting drug users. Thus, in 1996 the part of the sexual route of transmission was equal to 5.7 % cases, whereas the part of parenteral one consists of 77.1 % cases. Taking effective preventive measures against drug abuse has led to the decrease in the incidence of HIV-infection among this group of risk and changes of transmission routes. In 2015 in the structure of the leading transmission routes there were (22.6 ± 1.8) % of parenteral and (56.9 ± 2.1) % of sexual cases (p<0.05). These data indicate that the implementation tract infection due to injecting drug use leads to a concentrated stage of the HIV epidemic. At the same time the increase in the proportion of sexual transmission increase in the number of infected women indicate a threat to the output of the epidemic risk groups to the general set of the population. Conclusions. 1. The incidence of HIV-infection in the region was in several times lower than on the whole in Ukraine (accordingly 2.4 - 23.7 and 10.6 - 47.1 per 100 000 population). 2. Carried out research in the region revealed the peculiarities of the epidemic process of HIV-infection. So the level of growth of newly registered cases of HIV-infection from 0.1 per 100 000 population in 1995 to 20.5 per 100 000 population in 2015 was set (the growth rate was +7.0 %); a gradual change in the sexual spectrum of HIV-infected people (women from 12.9 % to 41.0 % and men from 87.1 % to 59.0 %) and the structure of the leading transmission routes (parenteral from 77.1 % to 22.6% and sexual from 5.7 % to 59.6 %); involvement in the epidemic process of all age groups with a predominance of the most working-age population 25 – 49 years. 3. The HIV epidemic is concentrated on the most vulnerable groups of population, but there is a risk of generalized spreading of HIV among the population. 4. Epidemiological surveillance of HIV infection must be adapted to the local epidemiological conditions, and preventive measures aimed at the timely detection of infection cases and the suspension of the epidemic.